Women in Irish Theatre: the Charabanc Theatre Company and Marie Jones - Bastos, Beatriz Kopschitz Xavier (ABEI Journal, 2007)
If women appear to have contributed relatively little to the theatricalscene in Ireland in the first half of the twentieth century, the same cannot be said about women in the Irish theatre after 1950. Increasing modernization, liberalization and decentralization of Irish society, and of the theatre industry, provided the opportunities for women’s voices to be included, not only in writing but also in producing and directing plays – that is to say, to play a role in Irish theatre’s social history. This paper focuses mainly on the work of the Charabanc Theatre Company, an all-female group founded in Belfast in 1983, and on the work of its former leading figure and writer, Marie Jones. Their work made a remarkable contribution to revitalizing the energy of Irish theatre in the closing decades of the twentieth century, leaving a significant legacy for national and international drama in the twenty-first century.